Use Of Digital Content As A Means To Reach Unreachable Market Segments Conventionally - Dony Ari Nugroho (Green Publisher Indonesia, 2024)
The presence of the industrial era 4.0 gave birth to various technological developments that have an influence on the delivery and processing of data in all aspects of human life. Technology brings the presence of developments in the field of marketing. This development comes with digital marketing that shifts conventional marketing. Business owners try to do various ways to develop their business and increase profits, one of which is the use of digital content as a strategy in digital marketing. The purpose of this study is to analyze the use of digital content as a means to reach market segments that are not conventionally reached. The research method used is qualitative with description processing. The data collection technique is a literature study using various relevant sources. The data obtained was analyzed with three stages, namely data reduction, data presentation, and conclusion making. The results show that the use of digital content as a digital marketing strategy is effective in reaching market segments that are not reached conventionally through social media platforms, websites, and mobile applications. Analysis of content performance and user interactions enables optimization of digital marketing strategies, increasing brand awareness, expanding reach, and enhancing engagement with diverse market segments, emphasizing the importance of continuous development and utilization of analytics technology to understand consumer preferences and behaviors to strengthen competitive positions in dynamic markets.